2023
DOI: 10.3389/fmed.2023.1078022
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 epidemiology, antibody dynamics, and neutralisation capacity in Irish healthcare workers in the era of booster COVID-19 vaccinations

Abstract: BackgroundThe PRECISE Study, a multi-phase cross-sectional seroprevalence study of anti-SARS-CoV-2 antibodies in Irish healthcare workers (HCW) investigated: (1) risk factors for SARS-CoV-2 seropositivity, (2) the durability of antibody responses in a highly vaccinated HCW cohort, and (3) the neutralisation capacity of detected antibodies, prior to booster COVID-19 vaccination.Materials and methodsSerology samples were collected across two hospital sites in November 2021 and analysed using the Roche Elecsys An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(68 reference statements)
2
4
0
Order By: Relevance
“…A statistically significant difference in ACE2-RBD binding inhibition was also demonstrated when stratified by the anti-S titre sub-groups “high” vs. “low.” A significant difference was not demonstrated between the anti-S titre sub-groups “negative” and “low” or “high” likely due to the small numbers of participants proving anti-S negative ( n = 3), and thus, robust conclusions from this result are difficult to draw. The PRECISE group has previously demonstrated that ACE2-RBD binding inhibition is highest in anti-S plus anti-N positive individuals ( 28 ), and this is again demonstrated here via the statistical correlation between anti-N titres and ACE2-RBD binding inhibition when assessed via Spearman rank correlation or anti-N titre sub-group assessment via a Kruskal–Wallis test with Dunn's multiple comparison test. Multiple other factors influence antibody neutralisation capacity, including COVID-19 vaccination/infection history ( 28 ) and other SARS-CoV-2 neutralising antibody targets, such as the N-terminal domain (NTD) ( 6 ).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…A statistically significant difference in ACE2-RBD binding inhibition was also demonstrated when stratified by the anti-S titre sub-groups “high” vs. “low.” A significant difference was not demonstrated between the anti-S titre sub-groups “negative” and “low” or “high” likely due to the small numbers of participants proving anti-S negative ( n = 3), and thus, robust conclusions from this result are difficult to draw. The PRECISE group has previously demonstrated that ACE2-RBD binding inhibition is highest in anti-S plus anti-N positive individuals ( 28 ), and this is again demonstrated here via the statistical correlation between anti-N titres and ACE2-RBD binding inhibition when assessed via Spearman rank correlation or anti-N titre sub-group assessment via a Kruskal–Wallis test with Dunn's multiple comparison test. Multiple other factors influence antibody neutralisation capacity, including COVID-19 vaccination/infection history ( 28 ) and other SARS-CoV-2 neutralising antibody targets, such as the N-terminal domain (NTD) ( 6 ).…”
Section: Discussionsupporting
confidence: 57%
“…The PRECISE group has previously demonstrated that ACE2-RBD binding inhibition is highest in anti-S plus anti-N positive individuals ( 28 ), and this is again demonstrated here via the statistical correlation between anti-N titres and ACE2-RBD binding inhibition when assessed via Spearman rank correlation or anti-N titre sub-group assessment via a Kruskal–Wallis test with Dunn's multiple comparison test. Multiple other factors influence antibody neutralisation capacity, including COVID-19 vaccination/infection history ( 28 ) and other SARS-CoV-2 neutralising antibody targets, such as the N-terminal domain (NTD) ( 6 ). It appears that this LFA POC cannot be relied upon solely to determine the neutralisation capacity of detected antibodies for a given individual.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The Prevalence of Antibodies to SARS-CoV-2 in Irish HCWs (PRECISE) study is a multicentre cross-sectional study of COVID-19 vaccine uptake and antibody response in HCWs [22][23][24]. Here, we investigate the demographic and epidemiological factors associated with primary vaccine uptake and receipt of additional booster vaccines in this population.…”
Section: Introductionmentioning
confidence: 99%